Agentes móveis inteligentes para suporte à umbiqüidade de serviços multimídia - Carvalho, Juliana Oliveira de (2006)
The telecommunications convergence with the network has allowed the availability of the services more and more sophisticated and by the services that be delivered, with quickness, agility, security, reliability and mainly that take into considerations the necessities of the users. In the context the service will be adaptable and sensible to the context, so they will be dependents of the personal, service and terminal mobility. Global mobility requires the coordination of a great variety of providers, warrant of compatibility among the backbone nets (Fix Telecom, Mobile Telecom and Internet) and acquisition of accordance among network operators. By this way users can have access to adapted services to their necessities from different localizations and devices. The use of the technology of intelligent mobile agents proportion autonomy and flexibility in the process of personalization and availability of services when it exists necessity of support to the personal and service mobility and enhance the distributed objects technology. This work starts from the architecture that establishes provides reference point, and proposes the use of distributed objects, paradigms and intelligent mobile agents to integrate communication environment that allows the access to a localization and devices. To evaluate the proposal, it implements a prototype where aspects of mobility and adaptation services are investigated.